Cobalt-free nickel hydroxide positive electrode material and preparation method thereof, positive electrode plate and nickel-metal hydride battery

By preparing a cobalt-free nickel hydroxide cathode material, a conductive network is formed using Ni(1-x1-y1)Znx1Xy1(OH)2 and expanded graphite, which solves the problems of high cost and uneven resource distribution caused by cobalt in nickel-metal hydride batteries and improves battery performance.

CN120933369AActive Publication Date: 2025-11-11SHENZHEN HIGHPOWER TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511465343.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-14
Publication Date
2025-11-11
Estimated Expiration
2045-10-14

AI Technical Summary

Technical Problem

Cobalt is an indispensable element in existing nickel-metal hydride batteries, which suffer from high cost, uneven resource distribution, and low safety.

Method used

The cobalt-free nickel hydroxide cathode material is used, and a conductive network with a porosity greater than 50% is formed by using the active material Ni(1-x1-y1)Znx1Xy1(OH)2 and the conductive agent expanded graphite. The preparation method includes solution mixing, reaction, purification and calcination steps.

Benefits of technology

It achieves good electrolyte wetting of the electrodes, forming a complete and interconnected conductive network, which improves the specific capacity and cycle life of the battery, solves the problems of low safety and high cost caused by cobalt resources, and eliminates dependence on cobalt.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_14
    Figure SMS_14
  • Figure SMS_15
    Figure SMS_15
  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

The invention provides a cobalt-free nickel hydroxide positive electrode material, a preparation method thereof, a positive electrode plate and a nickel-metal hydride battery, and aims to solve the problems of high cost and non-uniform resource distribution due to the fact that an existing Co material serves as an indispensable component of an existing nickel-metal hydride battery, and the cobalt-free nickel hydroxide positive electrode material comprises an active substance and a conductive agent, the active substance is a compound as shown in a chemical formula 1; the porosity of the conductive agent is greater than 50%; ni (1-x1-y1) Znx1Xy1 (OH) 2, wherein chemical formula 1 is shown in the specification; wherein x is greater than or equal to 0 and less than or equal to 0.1, y is greater than or equal to 0 and less than or equal to 0.05, and X is a metal element in the water-soluble metal salt and does not comprise Ni and Zn elements. The cobalt-free nickel hydroxide positive electrode material provided by the invention does not contain a cobalt element, so that the gram volume and the cycle life of a battery are remarkably improved; the problems of low safety, high cost, uneven resource distribution and the like caused by cobalt resources are solved, the dependence of a nickel-metal hydride battery positive electrode material on cobalt can be eliminated, and the influence and market opportunity of cobalt-free products are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nickel-metal hydride battery technology, and in particular to a cobalt-free nickel hydroxide cathode material, its preparation method, cathode sheet, and nickel-metal hydride battery. Background Technology

[0002] Nickel-metal hydride (Ni-MH) batteries possess advantages such as high specific energy, long cycle life, no memory effect, good overcharge and discharge resistance, high safety, good environmental compatibility, and a wide operating temperature range (-40-80℃). They are widely used in various portable electronic products, power tools, electric vehicles, modern military electronic equipment, and aerospace fields. Cobalt is an indispensable component in currently commercially available Ni-MH batteries, present in both the positive and negative electrodes. For the positive electrode, pure Ni(OH)₂ has low conductivity (approximately 10). -17 S cm -1 Cobalt is often used to improve conductivity and charging efficiency through surface coating and core solid solution. Furthermore, 0.1% to 10% cobalt suboxide is added during the subsequent positive electrode fabrication process to further enhance conductivity. For the negative electrode, cobalt is a component of most AB5-type hydrogen storage alloys, and it effectively inhibits alloy pulverization. Summary of the Invention

[0004] To address the issues of high cost and uneven resource distribution of existing Co materials, which are an indispensable component of nickel-metal hydride batteries, this application provides a cobalt-free nickel hydroxide cathode material, its preparation method, cathode sheet, and nickel-metal hydride battery.

[0005] On one hand, the present invention provides a cobalt-free nickel hydroxide cathode material, comprising an active material and a conductive agent, wherein the active material is a compound represented by chemical formula 1; and the conductive agent has a porosity > 50%. Ni (1-x1-y1) Zn x1 X y1 (OH)₂, chemical formula 1; Where 0≤x1≤0.1, 0≤y1≤0.05, X is a metal element in a water-soluble metal salt, and X does not include Ni and Zn elements.

[0006] Preferably, X is selected from one or more of Ca, Y, Mg, Ti, and Yb.

[0007] Preferably, the conductive agent is selected from expanded graphite, wherein the expanded graphite has a particle size of 5-100 μm, a porosity of 80-95%, and a specific surface area of ​​50-150 m². 2 / g; The particle size of the active substance is 5~50μm.

[0008] Preferably, the ratio of the D50 particle size D1 of the active material to the D50 particle size D2 of the expanded graphite is a, where a = D1 / D2; The expanded graphite includes one or more particle size ranges among 5~20μm, 20~40μm, 40~60μm, 60~80μm, and 80~100μm. The D50 particle size of the i-th particle size range is denoted as di, and the mass ratio of the i-th particle size range in the expanded graphite is denoted as fi, where i≥2. D2= , 0.15≤a≤2.

[0009] Preferably, the ratio of the mass of the active material to the mass of the expanded graphite is b; When the particle size of the expanded graphite is selected from one or both of 5~20μm and 20~40μm, b satisfies Equation 1. Formula 1; When the particle size of the expanded graphite is selected from at least one of 40~60μm, 60~80μm, and 80~100μm, or when the particle size of the expanded graphite is selected from at least one of 5~20μm and 20~40μm and at least one of 40~60μm, 60~80μm, and 80~100μm, b satisfies Equation 2. Formula 2; Electrode porosity is 20~40%; 15≤b≤23.4.

[0010] Secondly, this application provides a method for preparing the cobalt-free nickel hydroxide cathode material described above, comprising the following steps: Preparation of active substances: A solution A is obtained, which contains elements X, Ni, and Zn, wherein X is a metal element in a water-soluble metal salt and does not include Ni and Zn. A solution B is obtained, wherein solution B is an alkaline solution; The solutions A and B are mixed and reacted. After the reaction is completed, the active substance of the compound shown in chemical formula 1 is obtained by purification. A conductive agent is obtained, and the active material is mixed with the conductive agent to obtain the cobalt-free nickel hydroxide cathode material.

[0011] Preferably, obtaining solution A includes the following steps: A solution A is obtained by mixing a water-soluble metal salt containing X, a water-soluble metal salt containing Ni, and a water-soluble metal salt containing Zn in a molar ratio of y1:(1-x1-y1):x1 with water, wherein the molar concentration of solution A is 1~5 mol / L. The process of obtaining solution B includes the following steps: Solution B is obtained by mixing a caustic alkali and a complexing agent, wherein the concentration of the caustic alkali is 0.5~3 mol / L and the concentration of the complexing agent is 0.2~1 mol / L.

[0012] Preferably, the process of mixing and reacting solution A and solution B, followed by purification after the reaction to obtain the active substance of the compound shown in formula 1, includes the following steps: Mix the solutions A and B by stirring, adjust the pH to 8-11, and react at 50-80°C for 8-12 hours. After the reaction is complete, let the mixture stand for 8-24 hours. After standing, the solid substance is obtained by filtration and washing. The solid substance is dried at 60~100℃ for 8~24h to obtain solid powder. The solid powder is calcined at 200~500℃ for 3~5h. After calcination, it is pulverized to obtain the active substance of the compound shown in chemical formula 1.

[0013] Thirdly, this application provides a positive electrode sheet, comprising a positive electrode material, wherein the positive electrode material is the cobalt-free nickel hydroxide positive electrode material described above or prepared by the preparation method of the cobalt-free nickel hydroxide positive electrode material described above.

[0014] Fourthly, this application provides a nickel-metal hydride battery, including a negative electrode and the aforementioned positive electrode.

[0015] The cobalt-free nickel hydroxide cathode material provided in this application has the following effects: 1) The active material is a compound shown in Chemical Formula 1, which does not contain cobalt. The active material and the conductive agent enable the electrode to form a complete and interconnected conductive network while maintaining good electrolyte wetting, thereby achieving efficient utilization of the cathode active material and significantly improving the battery specific capacity and cycle life; 2) Neither the active material nor the conductive agent contains cobalt. When used in nickel-metal hydride batteries, it can solve the problems of low safety, high cost, and uneven resource distribution caused by cobalt resources. It can get rid of the dependence of nickel-metal hydride battery cathode materials on cobalt and enhance the influence and market opportunities of cobalt-free products. Detailed Implementation

[0016] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0017] To illustrate the technical solution of the present invention, specific embodiments are described below.

[0018] In one embodiment of the present invention, this application provides a cobalt-free nickel hydroxide cathode material, comprising an active material and a conductive agent, wherein the active material is a compound represented by chemical formula 1; and the conductive agent has a porosity > 50%. Ni (1-x1-y1) Zn x1 X y1 (OH)₂, chemical formula 1; Where 0≤x1≤0.1, 0≤y1≤0.05, X is a metal element in a water-soluble metal salt, and X does not include Ni and Zn elements.

[0019] Specifically, water-soluble metal salts refer to soluble salts that can dissolve in water at room temperature and contain metal elements.

[0020] The conductive agent has a porosity greater than 50% and a porous structure, which can be used to store electrolyte, increase the contact area between the electrolyte and the active material, and improve the wettability of the electrode to the electrolyte. The conductive agent has high conductivity and can form point-to-point or point-to-surface contact when mixed with the active material. The resulting electrode is conducive to forming a complete and interconnected conductive network and reducing the electrode impedance.

[0021] The cobalt-free nickel hydroxide cathode material provided in this application has the following effects: 1) The active material is a compound shown in Chemical Formula 1, which does not contain cobalt. The active material and the conductive agent enable the electrode to form a complete and interconnected conductive network while maintaining good electrolyte wetting, thereby achieving efficient utilization of the cathode active material and significantly improving the battery specific capacity and cycle life; 2) Neither the active material nor the conductive agent contains cobalt. When used in nickel-metal hydride batteries, it can solve the problems of low safety, high cost, and uneven resource distribution caused by cobalt resources. It can get rid of the dependence of nickel-metal hydride battery cathode materials on cobalt and enhance the influence and market opportunities of cobalt-free products.

[0022] In some embodiments, X is selected from one or more of Ca, Y, Mg, Ti, and Yb.

[0023] Specifically, X is selected from one or more of Ca, Y, Mg, Ti, and Yb, which can optimize the electrochemical performance of the cathode material, improve the structural stability of the cathode material, and improve the cycle performance of nickel-metal hydride batteries.

[0024] In some embodiments, the conductive agent is selected from expanded graphite, wherein the expanded graphite has a particle size of 5-100 μm, a porosity of 80-95%, and a specific surface area of ​​50-150 m². 2 / g; the particle size of the active substance is 5~50μm.

[0025] Specifically, the conductive agent is selected from expanded graphite with a particle size of 5~100μm and a specific surface area of ​​50~150m². 2 / g, expanded graphite has a layered structure that can coat the surface of active materials or intersperse between spherical active materials to form a continuous surface-to-point contact conductive network. This results in a good conductive network between the active material particles and the expanded graphite, and the resulting electrode can form a complete conductive network structure. At the same time, expanded graphite has good toughness, which can buffer the expansion of the active material. The porosity of expanded graphite is in the range of 80~95%, and its porous structure can increase the contact area between the electrolyte and the active material, and improve the wettability of the electrode to the electrolyte.

[0026] The particle size of expanded graphite is 5~100μm, which means the overall particle size range of expanded graphite is 5~100μm.

[0027] In some embodiments, the pore size of expanded graphite is 200~1300 nm.

[0028] Expanded graphite is available in several specifications based on particle size: 5-20 μm, 20-40 μm, 40-60 μm, 60-80 μm, and 80-100 μm. When the particle size of expanded graphite is 5-20 μm, the D50 particle size is 12.5 μm, the porosity is 95%, and the pore size is 200-400 nm. When the particle size of expanded graphite is 20-40 μm... The expanded graphite has the following particle sizes: μm, D50 particle size is 30μm, porosity is 91%, and pore size distribution is 400~600nm; expanded graphite has the following particle sizes: 40~60μm, porosity is 88%, pore size distribution is 600~800nm, D50 particle size is 50μm; expanded graphite has the following particle sizes: 60~80μm, D50 particle size is 70μm, porosity is 85%, pore size distribution is 800~1100nm; expanded graphite has the following particle sizes: 80-100μm, D50 particle size is 90μm, porosity is 80%, and pore size distribution is 1000~1300nm.

[0029] In some embodiments, the ratio of the D50 particle size D1 of the active material to the D50 particle size D2 of the expanded graphite is a, a = D1 / D2, and the particle size of the expanded graphite includes one or more particle size ranges among 5~20μm, 20~40μm, 40~60μm, 60~80μm, and 80~100μm. The D50 particle size of the i-th particle size range is denoted as di, and the mass ratio of the i-th particle size range in the expanded graphite is denoted as fi, i≥1; D2= , 0.15≤a≤2.

[0030] Specifically, a ratio α of the D50 particle size of the active material to that of the expanded graphite is in the range of 0.15 to 2. This is beneficial for the synergistic effect between the expanded graphite and the active material, and for the expanded graphite to coat the surface of the active material or intersperse between the spherical active materials, forming a continuous surface-to-point contact conductive network. This results in a better conductive network between the active material particles and the expanded graphite, and the resulting electrode can form a complete conductive network structure. At the same time, it is beneficial for the expanded graphite to store electrolyte, so that the electrode has a good electrolyte wetting effect.

[0031] If a is less than 0.15, the particle size of the expanded graphite is too large, and a continuous and interconnected conductive network structure cannot be formed between the active material and the expanded graphite. As a result, the electrode cannot form a complete conductive network structure, and the conductivity of the electrode is reduced. The active material cannot fully participate in the reaction, ion diffusion is hindered, and polarization increases. If a is greater than 2, the particle size ratio will block the electrode pores, affect electrolyte penetration, and reduce the battery cycle life.

[0032] The expanded graphite has a particle size range of 5~20μm, 20~40μm, 40~60μm, 60~80μm, 80~100μm, or one or more of these ranges. The D50 particle size of the i-th particle size range is denoted as di, and the mass ratio of the i-th particle size range in the expanded graphite is denoted as fi, where i≥2.

[0033] Specifically, when i=2, it means that the expanded graphite contains two particle size ranges, such as 5~20μm, 20~40μm, 40~60μm, 60~80μm, or 80~100μm. i=1 represents one of the two particle size ranges, recorded as expanded graphite 1, and i=2 represents the other, recorded as expanded graphite 2. For i=1, f1 is the mass of expanded graphite 1 divided by (mass of expanded graphite 1 + mass of expanded graphite 2), and d1 is the D50 particle size of expanded graphite 1. For i=2, f2 is the mass of expanded graphite 2 divided by (mass of expanded graphite 1 + mass of expanded graphite 2), and d2 is the D50 particle size of expanded graphite 2.

[0034] When i=3, it means that the expanded graphite contains three particle size ranges, such as 5~20μm, 20~40μm, 40~60μm, 60~80μm, or 80~100μm. These three particle size ranges are defined as expanded graphite 1, expanded graphite 2, and expanded graphite 3. f1 is the mass of expanded graphite 1 divided by (mass of expanded graphite 1 + mass of expanded graphite 2 + mass of expanded graphite 3), and d1 is the D50 particle size of expanded graphite 1. f2 is the mass of expanded graphite 2 divided by (mass of expanded graphite 1 + mass of expanded graphite 2 + mass of expanded graphite 3), and d2 is the D50 particle size of expanded graphite 2. f3 is the mass of expanded graphite 3 divided by (mass of expanded graphite 1 + mass of expanded graphite 2 + mass of expanded graphite 3), and d3 is the D50 particle size of expanded graphite 3. The calculation method is the same for i=4 and i=5, and will not be elaborated further here.

[0035] D2= When expanded graphite contains only one particle size range, i=1, and D2 is the corresponding particle size of D50. The ratio of the D50 particle size D1 of the active material to the D50 particle size D2 of the expanded graphite is a, where a = D1 / D2. When the expanded graphite contains only one particle size range, the corresponding D2 is the D50 particle size value corresponding to that particle size range. When the expanded graphite contains two or more particle size ranges, the corresponding D2 is expressed as D2 = The corresponding D2 value is obtained. For example, when expanded graphite contains two different particle size ranges, D2 is calculated as D2 = ((f1*d1) / ... -1.3 ) + (f2*d2) -1.3 )) (-1 / 1.3) f1 is the mass of expanded graphite 1 / (mass of expanded graphite 1 + mass of expanded graphite 2), and d1 is the D50 particle size in expanded graphite 1. i=2, f2 is the mass of expanded graphite 2 / (mass of expanded graphite 1 + mass of expanded graphite 2), and d2 is the D50 particle size in expanded graphite 2.

[0036] In some embodiments, the ratio of the mass of the active material to the mass of the expanded graphite is b; When the particle size of the expanded graphite is selected from one or both of 5~20μm and 20~40μm, b satisfies Equation 1. Formula 1; When the particle size of the expanded graphite is selected from at least one of 40~60μm, 60~80μm, and 80~100μm, or when the particle size of the expanded graphite is selected from at least one of 5~20μm and 20~40μm and at least one of 40~60μm, 60~80μm, and 80~100μm, b satisfies Equation 2. Formula 2; Electrode porosity is 20~40%; 15≤b≤23.4.

[0037] Specifically, the calculation method for b varies depending on the particle size range of the expanded graphite. When the particle size of the expanded graphite is in the range of 5–20 μm, or in the range of 20–40 μm, or a mixture of expanded graphite with particle sizes in the ranges of 5–20 μm and 20–40 μm, the formula used to calculate b is... , where a is the ratio of the D50 particle size D1 of the active material to the D50 particle size D2 of the expanded graphite.

[0038] Except for cases where the expanded graphite particle size is in the range of 5–20 μm, or the expanded graphite particle size is in the range of 20–40 μm, or a mixture of expanded graphite with particle sizes in the ranges of 5–20 μm and 20–40 μm, the b-value is calculated using the formula... The calculation is performed, where a is the ratio of the particle size D1 of the active material to the particle size D2 of the expanded graphite, and the electrode porosity is in the range of 20-40%.

[0039] The test method for electrode porosity is as follows: , where ρ 电极 ρ is the density of the electrode sheet (g / cm³), which is also the density of the positive electrode sheet. 材料 This represents the theoretical maximum density (g / cm³) of cobalt-free nickel hydroxide cathode material.

[0040] The electrode porosity here is the same as the porosity of the positive electrode. Different preparation methods of the positive electrode result in different electrode porosities. This application does not limit the preparation method of the positive electrode, as long as the porosity of the prepared positive electrode is in the range of 20-40%.

[0041] Specifically, the ratio b of the mass of the active material to the mass of expanded graphite satisfies the condition 15 ≤ b ≤ 23.4. This is beneficial for the active material and the conductive agent to form a continuous conductive network, making the electrode a complete and interconnected conductive network. This achieves efficient utilization of the positive electrode active material, significantly improving the battery's specific capacity and cycle life. If b is too large, the expanded graphite content is too low, resulting in dead zones in the active material due to lack of connection to the conductive network. If b is too small, excessive expanded graphite fills the electrode pores, hindering ion transport.

[0042] In some preferred embodiments, the cobalt-free nickel hydroxide cathode material simultaneously satisfies a) 0.15 ≤ a ≤ 2 and b) 15 ≤ b ≤ 23.4, and the specific surface area of ​​the expanded graphite is 50 m². 2 / g≤c≤150m 2Within the range of / g, it is beneficial for the active material and expanded graphite to form a continuous conductive network. The resulting electrode not only exhibits good electrolyte wettability but also has a complete and interconnected conductive network, thereby maximizing the utilization of the positive electrode active material. The assembled battery exhibits high specific capacity and long cycle life.

[0043] In some preferred embodiments, the cobalt-free nickel hydroxide cathode material is composed of an active material and a conductive agent.

[0044] Secondly, this application provides a method for preparing the cobalt-free nickel hydroxide cathode material described above, comprising the following steps: preparation: A solution A is obtained, which contains elements X, Ni, and Zn, wherein X is a metal element in a water-soluble metal salt and does not include Ni and Zn. A solution B is obtained, wherein solution B is an alkaline solution; The solutions A and B are mixed and reacted. After the reaction is completed, the active substance of the compound shown in chemical formula 1 is obtained by purification. A conductive agent is obtained, and the active material is mixed with the conductive agent to obtain the cobalt-free nickel hydroxide cathode material.

[0045] The preparation method of the cobalt-free nickel hydroxide cathode material provided in this application is simple. The active material of the compound shown in Chemical Formula 1 can be prepared by directly mixing it with a conductive agent to obtain the nickel hydroxide cathode material. The preparation method is simple and low-cost. The obtained cobalt-free nickel hydroxide cathode material can be used in batteries to effectively improve the specific capacity and cycle life of the battery. At the same time, the cathode material does not contain cobalt, which can solve the problems of low safety, high cost and uneven resource distribution caused by cobalt resources when used in nickel-metal hydride batteries. It can get rid of the dependence of nickel-metal hydride battery cathode materials on cobalt and enhance the influence and market opportunities of cobalt-free products.

[0046] In some embodiments, obtaining solution A includes the following steps: A solution A is obtained by mixing a water-soluble metal salt containing X, a water-soluble metal salt containing Ni, and a water-soluble metal salt containing Zn in a molar ratio of y1:(1-x1-y1):x1 with water, wherein the molar concentration of solution A is 1~5 mol / L. The process of obtaining solution B includes the following steps: Solution B is obtained by mixing a caustic alkali and a complexing agent, wherein the concentration of the caustic alkali is 0.5~3 mol / L and the concentration of the complexing agent is 0.2~1 mol / L.

[0047] Specifically, based on the structure shown in Chemical Formula 1, a water-soluble metal salt containing X, a water-soluble metal salt containing Ni, and a water-soluble metal salt containing Zn are mixed with water in a molar ratio of y1:(1-x1-y1):x1 to obtain solution A. The preparation method of solution A is simple. The molar concentration of solution A is 1~5 mol / L, which means that the molar amounts of X, Ni, and Zn contained in each liter of solution A are 1~5 mol.

[0048] Solution B is a mixed solution containing a caustic alkali and a complexing agent. The concentration of the caustic alkali is 0.5–3 mol / L, meaning the concentration of the caustic alkali in solution B is in the range of 0.5–3 mol / L. The concentration of the complexing agent is 0.2–1 mol / L, meaning the concentration of the complexing agent in solution B is in the range of 0.2–1 mol / L. The caustic alkali includes one or both of NaOH and KOH. The complexing agent includes one or both of ammonia and ammonium salts. The concentration of the caustic alkali in solution B can be in the following ranges: 0.5–1.0 mol / L, 1.0–1.5 mol / L, 1.5–2.0 mol / L, or 2.0–3.0 mol / L. The concentration of the complexing agent in solution B can be in the following ranges: 0.2–0.4 mol / L, 0.4–0.6 mol / L, 0.6–0.8 mol / L, or 0.8–1.0 mol / L. The ammonium salt includes one or more of ammonium sulfate.

[0049] Solution A contains metal elements X, Ni, and Zn, while solution B is an alkaline solution. When solutions A and B are mixed, nickel ions, zinc ions, and other metals react with hydroxide ions to form co-precipitates under alkaline conditions.

[0050] In some embodiments, the water-soluble metal salt containing X is selected from one or more of nitrates containing X, chlorides containing X, and sulfates containing X, wherein X does not contain Ni and Zn; The water-soluble metal salt containing Ni is selected from one or more of nickel nitrate, nickel chloride, and nickel sulfate; The water-soluble metal salt containing Zn is selected from one or more of zinc nitrate, zinc chloride, and zinc sulfate; The inorganic strong base includes sodium hydroxide, and the inorganic weak base includes ammonia.

[0051] Specifically, the water-soluble metal salt containing X is selected from one or more of nitrates containing X, chlorides containing X, and sulfates containing X, wherein X does not contain Ni and Zn; X is a metallic element in a water-soluble metal salt.

[0052] When X is selected from Ca, the nitrate containing X is calcium nitrate, the chloride containing X is calcium chloride, and the sulfate containing X is calcium sulfate. Similarly, when X is selected from Y, Mg, Ti, or Yb, the same logic applies.

[0053] Alkali metal hydroxides are selected from sodium hydroxide, potassium hydroxide, etc.

[0054] In some embodiments, mixing and reacting solutions A and B, followed by purification after the reaction to obtain the active substance of the compound represented by chemical formula 1, includes the following steps. Mix the solutions A and B by stirring, adjust the pH to 8-11, and react at 50-80°C for 8-12 hours. After the reaction is complete, let the mixture stand for 8-24 hours. After standing, the solid substance is obtained by filtration and washing. The solid substance is dried at 60~100℃ for 8~24h to obtain solid powder. The solid powder is calcined at 200~500℃ for 3~5h. After calcination, it is pulverized to obtain the active substance of the compound shown in chemical formula 1.

[0055] Specifically, mixing solution A and solution B can be achieved by slowly adding solution B dropwise to solution A while continuously stirring, or by slowly adding solution A to solution B while continuously stirring.

[0056] Adjusting the pH value to 8-11 is to create an alkaline environment, which allows nickel ions, zinc ions, etc., to react with hydroxide ions to form co-precipitates.

[0057] Within the temperature range of 50–80℃, it is favorable for nickel ions, zinc ions, etc., to react with hydroxide ions to form co-precipitates. The reaction temperature can be 50℃, 55℃, 60℃, 65℃, 70℃, 75℃, 80℃, etc. The reaction time can be 8–9h, 9–10h, 10–11h, or 11–12h.

[0058] After settling, filter to obtain filter cake. Wash the filter cake at least once with deionized water. The washing solution should be neutral to remove any possible impurity ions. After washing, a solid substance is obtained.

[0059] The solid material is placed in a drying device for drying at a temperature of 60-100℃ for 8-24 hours. After drying, a solid powder is obtained.

[0060] The dried solid powder was placed in a calcining apparatus and calcined at a temperature of 200–500 °C for 3–5 hours. This calcination temperature and time promoted crystal growth and the solid solution of element X in nickel hydroxide. After calcination, the powder was allowed to cool naturally to room temperature (15–35 °C), and then the product was pulverized to obtain Ni. (1-x1-y1) Zn x1 X y1 (OH) 2,Where 0≤x1≤0.1, 0≤y1≤0.05, X is a metal element in a water-soluble metal salt, and X does not include Ni and Zn elements.

[0061] Crushing includes grinding or ball milling.

[0062] In some embodiments, obtaining a conductive agent includes the following steps: Graphite, oxidant, inorganic acid and intercalating agent are mixed and reacted at 40-60℃ for 60-120 min. After the reaction is completed, the product A is washed to obtain product A. Product A is heated at 600~1000℃ for 5-30 s. After the heating is completed, it is pulverized to obtain the expanded graphite. The oxidant includes potassium permanganate, the inorganic acid includes concentrated sulfuric acid, and the intercalating agent includes ferric chloride; The volume of the inorganic acid added per gram of graphite is 3-5 ml; The mass ratio of graphite to oxidant is 1:(0.05~0.2). The mass ratio of graphite to intercalating agent is 1:(0.002~0.02). The graphite has a particle size of 1~50μm.

[0063] Specifically, in the preparation of the conductive agent, concentrated sulfuric acid is used as the intercalation carrier, providing intercalation ions and a reaction environment. Potassium permanganate is used as an oxidant to oxidize and activate the graphite layer, promoting intercalation. Iron oxide enhances the oxidation effect and optimizes the intercalation structure. The reaction is carried out at 40-60℃ for 60-120 min to obtain intercalated graphite. Then, the intercalated graphite is heated at 600~1000℃ for 5-30 s. The interlayer compounds decompose to generate gas, which drives the graphite layer to expand rapidly, resulting in porous expanded graphite.

[0064] The washing process to obtain product A after the reaction includes the following steps: After the reaction, sodium hydroxide solution is added for immersion washing for 30-60 minutes. After immersion washing, deionized water is used for washing until neutral, and then dried to obtain product A.

[0065] The process of obtaining expanded graphite by pulverizing after heating includes the following steps: ball milling at 200-2000 rpm for 10-30 minutes after heating to obtain expanded graphite.

[0066] The above-mentioned method for preparing conductive agents yields expanded graphite with a particle size of 5-100 μm, a porosity of 80-95%, and a specific surface area of ​​50-150 m². 2 / g.

[0067] The volume of the inorganic acid added per gram of graphite is in the range of 3-5 mL, which facilitates the addition of HSO4 in concentrated sulfuric acid. -SO4 2- It can be embedded between graphite layers in the reaction, providing intercalation ions and a reaction environment.

[0068] Controlling the mass ratio of graphite to oxidant to within the range of 1:(0.05~0.2) is beneficial for the oxidant to oxidize some carbon atoms on the surface and edge of the graphite layer. Moderate oxidation increases the active sites in the graphite layer, promoting the intercalation reaction. Specifically, the mass ratio of graphite to oxidant can be in the range of 1:(0.05~0.08), 1:(0.08~0.1), 1:(0.1~0.15), or 1:(0.15~0.2). By controlling the mass ratio of graphite to intercalating agent to be in the range of 1:(0.002~0.02), it synergistically enhances the oxidation effect and promotes the intercalation reaction in conjunction with the oxidant. Specifically, the mass ratio of graphite to intercalating agent can be in the range of 1:(0.002~0.008), 1:(0.008~0.01), 1:(0.01~0.015), or 1:(0.015~0.02). Thirdly, this application provides a positive electrode sheet, comprising a positive electrode material, wherein the positive electrode material is the cobalt-free nickel hydroxide positive electrode material described above or prepared by the preparation method of the cobalt-free nickel hydroxide positive electrode material described above.

[0069] The positive electrode sheet provided in this application contains cobalt-free nickel hydroxide positive electrode material. The active material and conductive agent enable the electrode to form a complete and interconnected conductive network while maintaining good electrolyte wetting, thereby achieving efficient utilization of the positive electrode active material and significantly improving the battery specific capacity and cycle life.

[0070] The positive electrode also includes additives and binders. The additives include one or more of TiO2, Y2O3, Yb2O3, Er2O3, Ca(OH)2, Tm2O3, and Lu2O3. The binders include one or more of carboxymethyl cellulose, carboxyethyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, sodium polyacrylate, polytetrafluoroethylene, styrene-butadiene rubber, sodium alginate, and chitosan.

[0071] Fourthly, this application provides a nickel-metal hydride battery, including a negative electrode and the aforementioned positive electrode.

[0072] The nickel-metal hydride battery provided in this application has a positive electrode material that does not contain cobalt. When used in nickel-metal hydride batteries, it can solve the problems of low safety, high cost, and uneven resource distribution caused by cobalt resources. It can eliminate the dependence of nickel-metal hydride battery positive electrode materials on cobalt, and enhance the influence and market opportunities of cobalt-free products. At the same time, the active materials and conductive agents contained in the positive electrode material can enable the electrodes to form a complete and interconnected conductive network while maintaining good electrolyte wetting, thereby achieving efficient utilization of the positive electrode active materials and significantly improving the specific capacity and cycle life of nickel-metal hydride batteries.

[0073] The preparation of the negative electrode sheet is a current technology and will not be elaborated here.

[0074] The present invention will be further illustrated by the following examples.

[0075] Example 1 1): Preparation of cathode materials S1: Preparation of active substances S11: Obtain solution A: Dissolve nickel nitrate, zinc nitrate, and magnesium nitrate in deionized water at a molar ratio of (1-x1-y1):x1:y1 to prepare a 2.0 mol / L mixed solution A; where x1=0.05, y1=0.02, and 1-x1-y1=0.93.

[0076] S12: Obtain solution B: Mix deionized water, sodium hydroxide, and ammonia water evenly to obtain solution B. In solution B, the concentration of sodium hydroxide is 2 mol / L and the concentration of ammonia water is 0.5 mol / L.

[0077] S13: Slowly add solution B to solution A while stirring continuously, adjust the pH to 10, react for 10 hours at a temperature of 60°C, and let stand for 15 hours after the reaction is complete; filter the precipitate and wash it repeatedly with deionized water until the washing solution is neutral to remove any possible impurity ions.

[0078] The cleaned solid material was placed in an oven and dried at 80°C for 18 hours. The dried solid powder was then placed in a muffle furnace and calcined at 300°C for 4 hours. After calcination, it was allowed to cool naturally to room temperature. The product was then ground at 800 rpm for 30 minutes to obtain Ni with a particle size of 5-30 μm. 0.93 Zn 0.05 Mg 0.02 (OH)2 active material. The D50 particle size of the active material is 18 μm.

[0079] S2: Preparation of expanded graphite 500g of natural graphite with a particle size of 1-50μm, 75g of potassium permanganate, and 5g of ferric chloride were added to 2.0L of concentrated sulfuric acid while stirring. The reaction was carried out at 50℃ for 80min. After the reaction, the graphite was washed with 0.3mol / L NaOH for 60min, washed with deionized water until neutral, and then dried to obtain expandable graphite. The expandable graphite was rapidly heated at 800℃ for 30s to obtain expanded graphite. The obtained expanded graphite was ball-milled at 1500rpm for 30min to obtain expanded graphite with a particle size of 20-40μm, a porosity of 91%, a specific surface area of ​​120m² / g, a pore size of 400-600nm, and a D50 particle size of 30μm.

[0080] S3: Preparation of cobalt-free nickel hydroxide cathode material Ni prepared in step S1 0.93 Zn 0.05 Mg 0.02 The cobalt-free nickel hydroxide cathode material is obtained by uniformly mixing (OH)2 active material and expanded graphite prepared in step S2. Ni is present in the mixture. 0.93 Zn 0.05 Mg 0.02 The ratio a of the D50 particle size D1 of (OH)2 and the D50 particle size D2 of expanded graphite is D1 / D2=0.6; Ni 0.93 Zn 0.05 Mg 0.02 The mass ratio of (OH)2 to expanded graphite is b= =23.4; 2) Preparation of positive electrode sheet 88 parts of the cobalt-free nickel hydroxide cathode material obtained in step S3, 2 parts of binder (carboxymethyl cellulose, carboxyethyl cellulose, hydroxyethyl cellulose), 2 parts of additives (TiO2, Y2O3, Yb2O3), and 3 parts of deionized water were sequentially added to a vacuum mixer. The mixing speed was controlled at 250 r / min and the mixture was stirred for 150 min to ensure that the cathode active material was evenly dispersed and to form a cathode slurry. The slurry was then processed through stretching, drying, pressing, and cutting to produce a cathode sheet.

[0081] 3) Preparation of negative electrode sheet Two parts of dispersant binder, two parts of negative electrode conductive agent, 92 parts of negative electrode active material, one part of negative electrode additive, and three parts of deionized water were added sequentially to a vacuum mixer. The mixing speed was controlled at 250 r / min, and the mixture was stirred for 120 min to ensure uniform dispersion of the active material. Then, three parts of polytetrafluoroethylene and 1.8 parts of styrene-butadiene rubber were added, and the mixture was stirred at a low speed of 200 r / min for 10 min to control the solid content of the slurry at 80%. The slurry was transferred to a slurry hopper, and the liquid level was maintained at 16 cm. A nickel-plated steel strip with a thickness of 0.06 mm was used as the substrate. After slurry pulling, drying, rolling, and cutting, the negative electrode sheet was produced.

[0082] The dispersant and binder is HPMC, the negative electrode conductive agent is 0.3% carbon black + 1.7% nickel powder, and the negative electrode active material is A2B7 alloy (its stoichiometric formula is La). 0.17 Pr 0.051 Nd 0.124 Sm 0.40 Y 0.01 Mg 0.15 Ni 3.28 Al 0.16 Zr 0.004 The negative electrode additive is Y2O3.

[0083] 4) Battery assembly The above positive electrode and negative electrode, and the surface density of 54 g / m² 2 A Japanese-imported diaphragm with a low sulfonation degree and added ultra-fine fibers, 0.15mm thick, is wound and implanted into a steel shell, and injected with OH- composed of potassium hydroxide / sodium hydroxide / lithium hydroxide / pure water. - An electrolyte with a concentration of 5.6 mol / L was used to seal and manufacture a 3A750 battery cell.

[0084] Example 2 This embodiment shares most of the same steps as Embodiment 1, except that the ball milling step in step S2 is different; the rest is the same as in Embodiment 1. Specifically, the obtained expanded graphite is divided into two parts. One part is ball-milled at 2000 rpm for 40 minutes, resulting in expanded graphite 2-1 with a particle size of 5-20 μm, a porosity of 95%, a pore size of 200-400 nm, a specific surface area of ​​150 m² / g, and a D50 particle size of 12.5 μm. The other part is ball-milled at 1500 rpm for 30 minutes, resulting in expanded graphite 2-2 with a particle size of 20-40 μm, a porosity of 91%, a specific surface area of ​​120 m² / g, a pore size of 400-600 nm, and a D50 particle size of 30 μm.

[0085] In the total expanded graphite, expanded graphite 2-1 accounts for 50% of the total expanded graphite by mass, and expanded graphite 2-2 accounts for 50% of the total expanded graphite by mass.

[0086] Example 3 This embodiment shares most of the same steps as Embodiment 1, except that the ball milling step in step S2 is different; the rest is the same as in Embodiment 1. Specifically, the obtained expanded graphite is divided into two parts. One part is ball-milled at 1000 rpm for 30 minutes, resulting in expanded graphite 3-1 with a particle size of 40-60 μm, a porosity of 88%, a pore size of 600-800 nm, a specific surface area of ​​100 m² / g, and a D50 particle size of 50 μm. The other part is ball-milled at 1500 rpm for 30 minutes, resulting in expanded graphite 3-2 with a particle size of 20-40 μm, a porosity of 91%, a specific surface area of ​​120 m² / g, a pore size of 400-600 nm, and a D50 particle size of 30 μm.

[0087] In the total expanded graphite, expanded graphite 3-1 accounts for 30% of the total expanded graphite by mass, and expanded graphite 3-2 accounts for 70% of the total expanded graphite by mass.

[0088] Example 4 This embodiment shares most of the same steps as Embodiment 1, except that the ball milling step in step S2 is different; the rest is the same as in Embodiment 1. Specifically, the obtained expanded graphite is divided into two parts. One part is ball-milled at 1300 rpm for 30 minutes, resulting in expanded graphite 4-1 with a particle size of 20-40 μm, a porosity of 91%, a pore size of 400-600 nm, a specific surface area of ​​120 m² / g, and a D50 particle size of 30 μm. The other part is ball-milled at 1000 rpm for 10 minutes, resulting in expanded graphite 4-2 with a particle size of 60-80 μm, a porosity of 85%, a specific surface area of ​​80 m² / g, a pore size of 800-1100 nm, and a D50 particle size of 70 μm.

[0089] Of the total expanded graphite, expanded graphite 4-1 accounts for 80% by mass and expanded graphite 4-2 accounts for 20% by mass.

[0090] Example 5 This embodiment shares most of the same steps as Embodiment 1, except that the ball milling step in step S2 is different; the rest is the same as in Embodiment 1. Specifically, in this embodiment, the obtained expanded graphite is ball-milled at 150 rpm for 10 minutes to obtain expanded graphite with a particle size of 90-120 μm, a porosity of 76%, a specific surface area of ​​40 m² / g, a pore size of 1300-1600 nm, and a D50 particle size of 110 μm. Ni... 0.93 Zn 0.05 Mg 0.02 The mass ratio of (OH)2 to expanded graphite is 23.4.

[0091] Example 6 The main steps of Example 6 are the same as those of Example 1, except that the values ​​of x1 and y1 are different, as shown in Table 1. The particle size of the active material obtained in step S13 is 5~25μm, and the D50 particle size is 16μm. The rest are the same as those of Example 1.

[0092] Example 7 The main steps of Example 7 are the same as those of Example 1, except that the values ​​of x1 and y1 are different, as shown in Table 1. The particle size of the active material obtained in step S13 is 5~25μm, and the D50 particle size is 15μm. The rest are the same as those of Example 1.

[0093] Example 8 Most of the steps in this embodiment are the same as those in Embodiment 1, except that in step S1 of this embodiment, the grinding speed is changed so that the D50 particle size of the active material is 12 μm; in step S2 of this embodiment, the grinding speed and ball milling time are adjusted to obtain expanded graphite with a particle size in the range of 5 to 100 micrometers and a D50 particle size of 90 μm. The rest are the same as in Embodiment 1.

[0094] Example 9 Most of the steps in this embodiment are the same as those in Example 1, with the following differences: In step S1 of this embodiment, the concentration of solution A in S11 is 1 mol / L; in S13, the reaction concentration is changed to 80°C; and the grinding speed is changed to achieve a D50 particle size of 30 μm for the active material. Furthermore, the ball milling step in S2 is different; by adjusting the speed and milling time, expanded graphite with a particle size in the range of 5–100 μm and a D50 particle size of 12.5 μm is obtained. The rest is the same as in Example 1.

[0095] Example 10 Most of the steps in this embodiment are the same as those in Embodiment 1, except that in step S1 of this embodiment, the grinding speed is changed so that the D50 particle size of the active material is 11 μm; in step S2 of this embodiment, the grinding speed and ball milling time are adjusted to obtain expanded graphite with a particle size in the range of 5 to 100 micrometers and a D50 particle size of 70 μm. The rest are the same as in Embodiment 1.

[0096] Example 11 Most of the steps in this embodiment are the same as those in Embodiment 1, except that in step S1 of this embodiment, the grinding speed is changed so that the D50 particle size of the active material is 6 μm; in step S2 of this embodiment, the grinding speed and ball milling time are adjusted to obtain expanded graphite with a particle size in the range of 5 to 100 micrometers and a D50 particle size of 30 μm. The rest are the same as in Embodiment 1.

[0097] Example 12 Most of the steps in this embodiment are the same as those in Embodiment 5, except that in step S1 of this embodiment, the grinding speed is changed so that the D50 particle size of the active material is 6 μm; in step S2 of this embodiment, the grinding speed and ball milling time are adjusted to obtain expanded graphite with a particle size in the range of 5 to 100 micrometers and a D50 particle size of 90 μm. The rest are the same as in Embodiment 1.

[0098] Example 13 This embodiment is largely the same as Embodiment 1, except that expanded graphite is not used as the conductive agent. Instead, natural graphite is purchased and used. The natural graphite has a particle size of 20-40 μm, a porosity of 65%, a specific surface area of ​​6 m² / g, and a D50 particle size of 28 μm. Ni 0.93 Zn 0.05 Mg 0.02 The mass ratio of (OH)2 to natural graphite remains 23.4.

[0099] Comparative Example 1 The main steps of this comparative example are the same as those of Example 1, except that the values ​​of x1 and y1 are different, as detailed in Table 1. The particle size of the active material obtained in step S13 of Comparative Example 1 is 5~30 μm, and the D50 particle size is 18 μm. The rest is the same as in Example 1.

[0100] Comparative Example 2 The main steps of this comparative example are the same as those of Example 1, except that the conductive agent in this comparative example is carbon black, and the porosity of the conductive agent is 35%. The rest are the same as those in Example 1.

[0101] Comparative Example 3 The main steps of this comparative example are the same as those of Example 1, except that this comparative example does not contain a conductive agent, while the rest are the same as those of Example 1.

[0102] The values ​​of a and b for the active materials and expanded graphite obtained in the above embodiments and comparative examples are shown in Table 1. The porosity of the positive electrode sheets obtained in each embodiment and comparative example is also shown in Table 1.

[0103] The porosity test method for the positive electrode sheet is as follows: Where ρ 电极 ρ represents the cathode density (g / cm³), and ρ_material represents the theoretical maximum density of the cobalt-free nickel hydroxide cathode material prepared in step S3.

[0104] Wherein, the positive electrode sheet density is the mass of the positive electrode active material layer divided by the volume of the positive electrode sheet.

[0105] The theoretical maximum density of cobalt-free nickel hydroxide cathode material = total mass of active material and conductive agent / total volume of active material and conductive agent.

[0106] Table 1 Note that in Example 5 above, the ratio of the mass of the added active material to the mass of the expanded graphite is directly and artificially limited to 23.4.

[0107] Performance testing The nickel-metal hydride batteries prepared in the above embodiments and comparative examples were subjected to the following performance tests.

[0108] Capacity Formation methods: (1) Charge at 150mA for 100min, then discharge at 150mA to 1.0V; (2) Charge at 75mA for 200min, then discharge at 150mA to 1.0V; (3) Charge at 150mA for 300min, then discharge at 150mA to 1.0V.

[0109] After formation, the nickel-metal hydride batteries of each embodiment and comparative example were subjected to three IEC capacity tests. The battery specific capacity was calculated as: (Third IEC capacity) / (Powder application amount). Powder application amount refers to the total mass of solid powder on the positive electrode.

[0110] 25℃ Cycling Performance The battery obtained above was charged at 750mA for 72 minutes, allowed to rest for 30 minutes, and then discharged at 750mA to 1V. This charge-discharge test was repeated until the battery capacity decreased to 60% of the first discharge capacity. The battery capacity was recorded after each cycle of the test.

[0111] The results of the above electrical performance tests are shown in Table 2.

[0112] Table 2 As can be seen from the test results in Tables 1 and 2, compared with Comparative Example 3, the cobalt-free nickel hydroxide cathode material only contains the compound shown in Chemical Formula 1 and does not contain a conductive agent, resulting in low specific capacity and poor cycle performance of the battery. Compared with Comparative Example 2, the conductive agent used in Comparative Example 2 is carbon black with a porosity of less than 50%, resulting in low specific capacity and poor cycle performance of the battery. Compared with Comparative Example 1, Examples 1, 6, and 7, x1 and y1 do not satisfy 0≤x1≤0.1 and 0≤y1≤0.05. Although the specific capacity of the battery is improved, the cycle life of the battery is still poor. This indicates that the compound shown in Chemical Formula 1 and the conductive agent with a porosity greater than 50% provided in this application can work together to enable the electrode to form a complete and interconnected conductive network while maintaining good electrolyte wetting, thereby achieving efficient utilization of the positive electrode active material and significantly improving the specific capacity and cycle life of the battery.

[0113] Comparing Examples 1-4 and Examples 8-9, by changing the rotation speed and ball milling time, although the expanded graphite particle size in Examples 8 and 9 was in the range of 5-100 micrometers, the resulting batteries had low specific capacity and low cycle life. This indicates that 'a' does not satisfy 0.15≤a≤2, meaning a continuous interconnected conductive network structure cannot be formed between the active material and the expanded graphite. Consequently, the electrodes cannot form a complete conductive network structure, reducing electrode conductivity. Furthermore, the active material cannot fully participate in the reaction, hindering ion diffusion, increasing polarization, and reducing battery cycle life. Comparing Examples 1-4 and Examples 10-11, by changing the ball milling and rotation speed, the expanded graphite particle size was still in the range of 5-100 micrometers. However, the value of 'b' obtained according to the formula was not in the range of 15-23.4, resulting in poor specific capacity and cycle life for the batteries. It is speculated that if 'b' is too small, excessive expanded graphite fills the electrode pores, hindering ion transport; if 'b' is too large, the expanded graphite content is low, leading to dead zones in the active material due to lack of a connected conductive network, also reducing battery cycle life. This suggests that using the formula... or formula Calculations show that the ratio of the mass of the active material to the mass of the expanded graphite, b, satisfies the condition 15 ≤ b ≤ 23.4. This is beneficial for the formation of a continuous conductive network between the active material and the conductive agent, resulting in a complete and interconnected conductive network in the electrode. This leads to efficient utilization of the positive electrode active material and significantly improves the battery's specific capacity and cycle life. A comparison of Examples 1-4 and Examples 12 and 5 illustrates that it is hypothesized that neither the values ​​of a and b obtained from the formulas for a and b, nor the defined value of b, can match the actual particle size of the added expanded graphite with the particle size of the active material, ensuring better and more uniform mixing. This may affect the integrity of the conductive network, thereby reducing the battery's cycle life. It is indicated that the particle size range of the expanded graphite is 5~100 μm, and the particle size of the active material is 5~50 μm. Calculating the values ​​of a and b using the relationship defined in this application, a satisfies 0.15 ≤ a ≤ 2, and b satisfies 15 ≤ b ≤ 23.4. The resulting battery exhibits high energy density and good cycle performance.

[0114] Comparing Example 1 and Example 13, Example 13 uses natural graphite. Although the porosity of natural graphite is greater than 50%, the energy density and cycle life of the battery are low. This shows that the reasonable composition of the compound shown in Formula 1 of this application and the expanded graphite conductive agent can enable the electrode to form a complete and interconnected conductive network while maintaining good electrolyte wetting, thereby achieving efficient utilization of the positive electrode active material and significantly improving the battery specific capacity and cycle life.

[0115] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. These modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention, and should all be included within the protection scope of the present invention.

Claims

1. A cobalt-free nickel hydroxide cathode material, characterized in that, It includes an active substance and a conductive agent, wherein the active substance is a compound shown in Formula 1; and the conductive agent has a porosity > 50%. Ni (1-x1-y1) Zn x1 X y1 (OH)₂, chemical formula 1; Where 0≤x1≤0.1, 0≤y1≤0.05, X is a metal element in a water-soluble metal salt, and X does not include Ni and Zn elements.

2. The cobalt-free nickel hydroxide cathode material according to claim 1, characterized in that, X is selected from one or more of Ca, Y, Mg, Ti, and Yb.

3. The cobalt-free nickel hydroxide cathode material according to claim 1, characterized in that, The conductive agent is selected from expanded graphite, which has a particle size range of 5~100μm, a porosity of 80~95%, and a specific surface area of ​​50~150m². 2 / g; The particle size of the active substance is 5~50μm.

4. The cobalt-free nickel hydroxide cathode material according to claim 3, characterized in that, The ratio of the D50 particle size D1 of the active material to the D50 particle size D2 of the expanded graphite is a, where a = D1 / D2. The expanded graphite includes one or more particle size ranges among 5~20μm, 20~40μm, 40~60μm, 60~80μm, and 80~100μm. The D50 particle size of the i-th particle size range is denoted as di, and the mass ratio of the i-th particle size range in the expanded graphite is denoted as fi, where i≥2. D2= 0.15 ≤ a ≤ 2.

5. The cobalt-free nickel hydroxide cathode material according to claim 4, characterized in that, The ratio of the mass of the active material to the mass of the expanded graphite is b; When the particle size of the expanded graphite is selected from one or both of 5~20μm and 20~40μm, b satisfies Equation 1. Formula 1; When the particle size of the expanded graphite is selected from at least one of 40~60μm, 60~80μm, and 80~100μm, or when the particle size of the expanded graphite is selected from at least one of 5~20μm and 20~40μm and at least one of 40~60μm, 60~80μm, and 80~100μm, b satisfies Equation 2. Formula 2; Electrode porosity is 20~40%; 15≤b≤23.4。 6. A method for preparing the cobalt-free nickel hydroxide cathode material according to any one of claims 1 to 5, characterized in that, Includes the following steps: Preparation of active substances: A solution A is obtained, which contains elements X, Ni, and Zn, wherein X is a metal element in a water-soluble metal salt and does not include Ni and Zn. A solution B is obtained, wherein solution B is an alkaline solution; The solutions A and B are mixed and reacted. After the reaction is completed, the active substance of the compound shown in chemical formula 1 is obtained by purification. A conductive agent is obtained, and the active material is mixed with the conductive agent to obtain the cobalt-free nickel hydroxide cathode material.

7. The method for preparing the cobalt-free nickel hydroxide cathode material according to claim 6, characterized in that, The process of obtaining solution A includes the following steps: A solution A is obtained by mixing a water-soluble metal salt containing X, a water-soluble metal salt containing Ni, and a water-soluble metal salt containing Zn in a molar ratio of y1:(1-x1-y1):x1 with water, wherein the molar concentration of solution A is 1~5 mol / L. The process of obtaining solution B includes the following steps: Solution B is obtained by mixing a caustic alkali and a complexing agent, wherein the concentration of the caustic alkali is 0.5~3 mol / L and the concentration of the complexing agent is 0.2~1 mol / L.

8. The method for preparing the cobalt-free nickel hydroxide cathode material according to claim 6, characterized in that, The process of mixing and reacting solutions A and B, followed by purification after the reaction to obtain the active substance of the compound represented by chemical formula 1, includes the following steps. Mix the solutions A and B by stirring, adjust the pH to 8-11, and react at 50-80°C for 8-12 hours. After the reaction is complete, let the mixture stand for 8-24 hours. After standing, the solid substance is obtained by filtration and washing. The solid substance is dried at 60~100℃ for 8~24h to obtain solid powder. The solid powder is calcined at 200~500℃ for 3~5h. After calcination, it is pulverized to obtain the active substance of the compound shown in chemical formula 1.

9. A positive electrode plate, characterized in that, The cathode material is a cobalt-free nickel hydroxide cathode material as described in any one of claims 1-5 or prepared by the preparation method of the cobalt-free nickel hydroxide cathode material as described in any one of claims 6-8.

10. A nickel-metal hydride battery, characterized in that, It includes the negative electrode and the positive electrode as described in claim 9.

Citation Information

Patent Citations

  • Preparation method and application of nickel hydroxide positive electrode material

    CN110943221A

  • Positive electrode material of nickel-metal hydride battery, preparation method of positive electrode material, nickel-metal hydride battery and electric equipment

    CN119092710A

  • Cobalt-free alkaline secondary battery

    JP2012204177A

  • Coated Nickel Hydroxide Powder as Cathode Active Material for Alkaline Secondary Battery and Method for Producing the Same

    US20120276453A1